2014
DOI: 10.1124/dmd.114.059766
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronosyltransferase 1a Enzymes Are Present and Active in the Mouse Blastocyst

Abstract: The UDP-glucuronosyltransferase (UGT) enzymes are critical for regulating nutrients, hormones, and endobiotics, as well as for detoxifying xenobiotics. Human and murine fetuses are known to express glucuronidation enzymes, but there are currently no data prior to implantation. Here we addressed this gap in knowledge and tested whether Ugt enzymes are already present in preimplantation-stage embryos. Blastocysts were obtained after in vitro fertilization with gametes from B6D2F1 hybrid mice and from embryo cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…When discussing ontogeny, the profound effects of steroidal axes activating in adolescence is sometimes lost in the rush to discern molecular genetic effects. There is evidence that several of the UGT1A and 2B isoforms can be induced by sex steroids and sex steroid precursors such as gonadotropin‐releasing hormone . Certainly, these data support the contention that part of the ontogenetic process for activating UGTs may be the increase in steroids in adolescence, at least as far as UGT coexpression is concerned, as we found clear breakpoints in the data for correlations at or around 12 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…When discussing ontogeny, the profound effects of steroidal axes activating in adolescence is sometimes lost in the rush to discern molecular genetic effects. There is evidence that several of the UGT1A and 2B isoforms can be induced by sex steroids and sex steroid precursors such as gonadotropin‐releasing hormone . Certainly, these data support the contention that part of the ontogenetic process for activating UGTs may be the increase in steroids in adolescence, at least as far as UGT coexpression is concerned, as we found clear breakpoints in the data for correlations at or around 12 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…Buckley et al [55] have shown that Ugt1a, Ugt2a, Ugt2b and Ugt3a are expressed in mouse placenta. Although studies of rodent fetal livers showed glucuronidation activity, expression of specific Ugt isoforms in mouse fetal livers has not yet been fully described [56, 57]. In Abcb1a -/- / 1b -/- and Abcb1a -/- / 1b -/- / Abcg2 -/- mice, maternal plasma AUC of NBUP-G was increased 3-4-fold compared to wild-type mice (Table 2); however, fetal AUC of NBUP-G was increased only 1.7-2.0-fold (Table 5), indicating a low membrane permeability of NBUP-G which makes sense as NBUP-G is much more water soluble than its parent NBUP.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, UDP-UGT is another enzyme associated with detoxification (130), which was found to be increased by parathion (UGT1A1 and UGT2B genes) and decreased by estrogen; however, there was no difference in these genes when the substances were used together (34). Clinical studies have shown an increase in the UGT1A1 and UGT2B gene expression in ovarian cancer (119); therefore, it can be a reliable molecular biomarker for the risk of cancer.…”
Section: Parathion and Malathion Induce Metabolic Alterationsmentioning
confidence: 67%